Cardiac Effects of Parkinson's Diseasec - Hüsnü Değirmenci; Eftal Murat Bakirci; Hikmet Hamur (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2020)
Parkinson's disease, which has symptoms and signs such as tremor, bradykinesia, rigidity and postural instability, is the most common neurodegenerative disease after Alzheimer's disease. In Parkinson's disease, pathological mechanisms such as abnormal accumulation of protein aggregates, disruption of protein clearance pathways, oxidative stress, neuroinflammation, mitochondrial damage and genetic mutations lead to the formation of the clinic. Coronary artery disease, heart failure, cardiac autonomic dysfunction, heart failure, sudden death and hypertension can be seen in Parkinson's disease. Parkinson's disease leads to an increased risk of morbidity and mortality associated with these diseases. Dopaminergic drugs, non-dopaminergic drugs, growth factor support, stem cell therapy, gene therapy, exercise, diet and surgical treatment play an important role in the treatment of Parkinson's disease. This treatment helps to reduce cardiac effects.